2020
DOI: 10.3390/atmos11060664
|View full text |Cite
|
Sign up to set email alerts
|

The Polar Vortex and Extreme Weather: The Beast from the East in Winter 2018

Abstract: Public attention has recently focused on high-impact extreme weather events in midlatitudes that originate in the sub-Arctic. We investigate movements of the stratospheric polar vortex (SPV) and related changes in lower atmospheric circulation during the February-March 2018 “Beast from the East” cold winter event that dramatically affected much of Europe and north-central North America. This study demonstrates that the movement of the SPV is a key linkage in late winter subarctic and northern midlatitude extre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 35 publications
1
22
0
Order By: Relevance
“…Focusing on SSW impacts on European weather, cold air outbreaks can occur over Eurasia and northwestern (NW) Europe (Kolstad et al 2010; Lehtonen & Karpechko, 2016; Mitchell et al., 2013; Tomassini et al., 2012). For example, the “Beast from the East” cold air outbreak over NW Europe at the start of March 2018 was associated with a SSW onset in mid‐February (e.g., Karpechko et al., 2018; Overland et al., 2020). Kolstad et al.…”
Section: Introductionmentioning
confidence: 99%
“…Focusing on SSW impacts on European weather, cold air outbreaks can occur over Eurasia and northwestern (NW) Europe (Kolstad et al 2010; Lehtonen & Karpechko, 2016; Mitchell et al., 2013; Tomassini et al., 2012). For example, the “Beast from the East” cold air outbreak over NW Europe at the start of March 2018 was associated with a SSW onset in mid‐February (e.g., Karpechko et al., 2018; Overland et al., 2020). Kolstad et al.…”
Section: Introductionmentioning
confidence: 99%
“…This anomalous warming event occurred coincidently after the sudden stratospheric warming (SSW) event observed in mid-February 2018 (Moore et al, 2018;Rao et al 2018), which developed into a vortex split (Lü et al, 2020). Subsequently, the winter weather was severe with intense cold air across Europe in March 2018 (Overland et al, 2020). Although the exact cause of SSW variability in still under debate, SSWs are generally known to cause anomalous warming over Greenland and impact surface weather patterns down to mid-latitudes (Butler et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…It was nevertheless preceded by a preliminary planetary wave pulse in mid-January, primarily from wave-1 (Lü et al, 2020;Xie et al, 2020). While the pronounced impacts of the SSW in the troposphere in the form of cold air outbreaks over Europe, Asia and North America in February and March have been studied (Karpechko et al, 2018;Lü et al, 2020;Overland et al, 2020;Knight et al, 2020), there have been few studies of the stratosphere-mesosphere coupling during this event. A notable exception is Wang et al (2019) who observed the mesospheric zonal wind reversal and carbon monoxide (CO) abundance in the layer 70-85 km using ground-based microwave remote sensing at a mid-latitude site.…”
Section: Winter 2017-2018mentioning
confidence: 99%